Addressing health care disruption in rural Mozambique due to extreme climate events: mobile units tackling cyclones, vaccine-preventable diseases, and beyond - Rossi, Benedetta; Formenti, Beatrice; Cerini, Carlo; Tique, Nerisia; da Celma Cossa, Rafaela; Boniotti, Federica; Comini, Bruno; Tomasoni, Lina Rachele; Castelli, Francesco (Frontiers in Tropical Diseases, 2024)
Floods, and cyclones are occurring with increasing frequency and intensity worldwide due to global warming. Mozambique is very susceptible to these extreme events due to its geographical location. In the last ten years, four of the most severe extreme climatic events have been observed in this country, leading to widespread destruction of infrastructure and the displacement of inhabitants. Cyclones Dineo in 2017, Idai and Kenneth in 2019 and recently Freddy in 2023 affected in total over two million people impacting food and water security, causing cholera outbreaks and damage to health facilities. The mobile health units, known as Brigadas Móveis (BM), are crucial to the Mozambican health system as they provide people in the most remote areas with vaccinations, and antimalarials, and other interventions. The BM activities in five districts of Inhambane province in the south of Mozambique are run by the NGO Medicus Mundi Italia in collaboration with the local health authorities. Cyclone Freddy flooded the province of Inhambane, affecting road accessibility and the BM’s planned operations in all five districts with a loss of 37.8% of BM outreach activities. The temporary absence of the BM service resulted in rural communities having no access to health care, including routine vaccine administration. Adaptation strategies need to be implemented to address the healthcare challenges associated with extreme climate events. As described in our experience in Inhambane, BM restored outreach activities immediately after the cyclone, improving access to care after challenging situations.